The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1039/d0dt02731f
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-structural studies of an unusual [MnIIIMnIIGdIII(OR)4]4− partial cubane from 2,2′-bis-p-tBu-calix[4]arene

Abstract: A co-ligand guides the formation of an unusual bis-calix[4]arene-supported cluster with a unique triangular MnIIIMnIIGdIII core.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…It is worth mentioning that Mn-Ln complexes containing only Mn(II) ions are quite uncommon compared to Mn(III)-Ln(III) and Mn(III)/Mn(II)-Ln(III) counterparts. 12 The aim of this work is threefold: (i) To establish magneto-structural correlations for the simple Mn(II)Gd(III) dinuclear complexes; (ii) To analyze how magnetothermal properties of this family of closely related Mn(II)Gd(III) based compounds are influenced by the magnitude and sign of the magnetic exchange coupling and (iii) To know if the large anisotropy of the Dy(III) ions, together with the coupling to paramagnetic isotropic Mn(II) ions, could lead to the presence of SMM behaviour in the Dy(III) derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that Mn-Ln complexes containing only Mn(II) ions are quite uncommon compared to Mn(III)-Ln(III) and Mn(III)/Mn(II)-Ln(III) counterparts. 12 The aim of this work is threefold: (i) To establish magneto-structural correlations for the simple Mn(II)Gd(III) dinuclear complexes; (ii) To analyze how magnetothermal properties of this family of closely related Mn(II)Gd(III) based compounds are influenced by the magnitude and sign of the magnetic exchange coupling and (iii) To know if the large anisotropy of the Dy(III) ions, together with the coupling to paramagnetic isotropic Mn(II) ions, could lead to the presence of SMM behaviour in the Dy(III) derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…The DFT computed spin density suggests dominant spin delocalization on the Co­(II) centers with the spin density of 2.749 (Figure d and Figure S11), and the singly occupied π* s -tetrazine radical orbital is energetically close to the Co­(II) 3d orbitals . Furthermore, the overlap integral (| S ab |) calculations by using the singly occupied ligand and metal-based molecular orbitals , demonstrated that out of the three possible Co­(II)–radical ( s -tetrazine) interactions one of the interactions is really strong (Co­(d xy )|p|Rad­(π*) = 0.218, Figure e and Figure S12), dominating the strong AF interaction. It should be mentioned that both the DFT and ab initio calculations suggest the presence of small AF interaction between the Co­(II) ions, as stated previously in several related complexes .…”
Section: Resultsmentioning
confidence: 97%
“…20 The magnitude and sign of the magnetic exchange interactions can also be related to the calculated average total overlap integral (∑|Sa(3d)b(3d)|/n, Figure S12). 21 The smaller the average total overlap integral, the larger the ferromagnetic interaction (or the smaller the antiferromagnetic interaction) and vice versa. Note that for the J3 interaction, the JT axes of the Mn III ions lie perpendicular to each other, with one lying parallel to the bridging plane and the other perpendicular to the bridging plane.…”
Section: Resultsmentioning
confidence: 99%